Leukaemia Cutis: Clinical Features and Outcomes of 56 Patients - Hwa Jung Yook; Joon Ho Son; Yeong Ho Kim; Ju Hee Han; Ji Hyun Lee; Young Min Park; Nack-Gyun Chung; Hee Je Kim; Chul Hwan Bang (Medical Journals Sweden, 2022)
Leukaemia is a malignant neoplasm of the haematopoietic system. Cutaneous manifestations of leukaemia are called leukaemia cutis, and are regarded as a sign of poorer prognosis and shorter survival time. A single-institution retrospective review was performed of medical records of patients diagnosed with leukaemia cutis in the dermatology department of Seoul St Mary's Hospital between January 2012 and April 2021. Fifty-six cases with cutaneous leukaemic involvement and underlying haematological malignancy were included (40 acute myelogenous leukaemia, 8 acute lymphoblastic leukaemia, 3 chronic myeloid leukaemia, 2 chronic lymphocytic leukaemia, and 3 myelodysplastic syndrome). Male-female ratio 1.9:1, mean age at diagnosis 45.8 years. Plaques (28%) and papules (27%) were the most common skin lesions, followed by patches (18%) and nodules (16%). Mean time from diagnosis of leukaemia to development of leukaemia cutis was 12.3 months. Forty-six patients (84%) died during the 7-year follow-up; mean time from diagnosis of leukaemia cutis to death was 5.4 months. The results suggest that leukaemia cutis is associated with poor outcomes in patients with leukaemia. Comprehensive skin examination of these patients may help diagnose leukaemia cutis early, enabling prompt treatment.